La violencia obstétrica: rutas de reparación en las comisiones estatales de derechos humanos en San Luis Potosí, México - María de Lourdes Alejandra Miranda-Herrera; Andrés Alcalá (Universitat de Barcelona, 2023)
Towards the language analysis performed on two recommendations issued by the local human rights commission located in San Luis Potosí, México, this paper pretends to uncover the institutional dimension of obstetric violence which acts on a local level of health authorities. The analysis stands by a concept of obstetric violence as a systematic violences accumulation committed on the women's bodies produced by an (undiminished) hospital-structural failure; but also, a poor performs on the medical state public services affected by the communitarian and political life of those women. This analysis also involves the human rights dimension of women on this form of violence, which stands on the before said, local level of healthcare public system. The research was structured with a qualitative approach through the selection of secondary information sources towards two recommendations issued by the human rights' local authority. The information sources were purely based on the content of the violations present on each document, taking on consideration the human right gross violations and the quality of the recommendations.